Synthesis and Application of Smart Polymers in Architectural Coatings - Carney, Colton; Castel, Cole; Ramsey, Jacob; Glogowski, Elizabeth M. (My University, 2019)
The focus of this research has been the synthesis and use of “smart” diblock copolymers as dispersants in architectural coatings such as paints, primers, and stains. Smart polymers are stimuli-responsive and change properties based on the surrounding environment. These polymers are expected to perform as smart dispersants to enhance the dispersion of titanium dioxide. Dispersants are substances designed to prevent suspended particles from aggregating. Titanium dioxide is an industry standard to produce white pigmented materials. Poly(2- dimethylaminoethyl methacrylate) (PDMAEMA) has the ability to flip between being hydrophobic or hydrophilic as temperature and pH are altered. Diblock copolymers of PDMAEMA and polyethylene glycol (PEG) were synthesised using atom transfer radical polymerization (ATRP). Gel Permeation Chromatography (GPC) and Nuclear Magnetic Resonance (NMR) Spectroscopy were used to determine if targeted chain lengths were reached. The properties of the various smart polymers were examined with a variety of methods. Viscosity, interfacial tension, and dynamic light scattering (DLS) techniques were used to analyze the diblock copolymer characteristics in varied environments. Ultimately, PDMAEMA copolymers will be evaluated as smart dispersants for titanium dioxide in architectural coating applications.
Color poster with text, images, charts, and graphs.
Keywords: Smart polymers; Protective coatings; Posters